Impact of River Mining: A Case Study of Itram River, Surkhet - Regmi, Kiran Raj (Academia Research Journal, 2025)
The demand for sand and gravel is increasing in many parts of the world due to rapid urbanization and economic development for infrastructural building activities. It has resulted in rapid extraction of stone, sand and gravel from river areas, leading to serious effects on river basin environments as well as nearby communities. Nevertheless, socio-economically, some local miners are also benefited by material extraction from the river. The lack of adequate information on the impacts of sand and gravel extraction is a major challenge in the environmental sectors of the developing countries. This study highlights the impacts of mining activities in the Itram River of Birendranagar, -12, Surkhet. Field observations and an interview guide were administered among 30 dwellers of riparian community of Itram to collect qualitative data, which focused on the identification of positive and negative impacts emerging from river mining activities. Few local people who are involved in mining activities are benefited. Except them, most of the local people conveyed the highest magnitude of negative impacts regard mining activities. Therefore, it is suggested to control mining activities and river encroachment to preserve the drainage system and riverine environment for the riparian community.